The XFP (17‐BM) beamline for X‐ray footprinting at NSLS‐II. (11th June 2019) - Asuru, Awuri; Farquhar, Erik R.; Sullivan, Michael; Abel, Donald; Toomey, John; Chance, Mark R.; Bohon, Jen
Abstract : The development of a high‐flux beamline for X‐ray footprinting at NSLS‐II is presented. Abstract : Hydroxyl‐radical mediated synchrotron X‐ray footprinting (XF) is a powerful solution‐state technique in structural biology for the study of macromolecular structure and dynamics of proteins and nucleic acids, with several synchrotron resources available to serve the XF community worldwide. The XFP (Biological X‐ray Footprinting) beamline at the NSLS‐II was constructed on a three‐pole wiggler source at 17‐BM to serve as the premier beamline for performing this technique, providing an unparalleled combination of high flux density broadband beam, flexibility in beam morphology, and sample handling capabilities specifically designed for XF experiments. The details of beamline design, beam measurements, and science commissioning results for a standard protein using the two distinct XFP endstations are presented here. XFP took first light in 2016 and is now available for general user operations through peer‐reviewed proposals. Currently, beam sizes from 450 µm × 120 µm to 2.7 mm × 2.7 mm (FWHM) are available, with a flux of 1.6 × 10 16 photons s −1 (measured at 325 mA ring current) in a broadband (∼5–16 keV) beam. This flux is expected to rise to 2.5 × 10 16 photons s −1 at the full NSLS‐II design current of 500 mA, providing an incident power density of >500 W mm −2 at full focus.